An innovative scheme for sub-50 nm patterning via electrohydrodynamic lithography. Issue 33 (22nd June 2017) - Lee, Suok; Jung, Sanghee; Jang, A-Rang; Hwang, Jaeseok; Shin, Hyeon Suk; Lee, JaeJong; Kang, Dae Joon
Abstract : we report a low-cost, simple, direct writing nanopatterning via electrohydrodynamic lithography with great fidelity for obtaining sub-50 nm nanostructures. Abstract : The fabrication of large-area and well-ordered nanostructures using lithographic techniques is challenging. We have developed novel approaches for sub-50 nm nanopatterning using an electrohydrodynamic lithography (EHL) technique by tailoring experimental parameters such as applied voltage, stamp features, filling ratio, and choice of resist film. We obtain a sub-50 nm pattern replica from a master stamp that contains an array of line patterns having 50 nm widths. Moreover, we show that a far-smaller pattern replication than the original pattern size can be readily obtained by carefully adjusting the experimental conditions. Perfect- and much smaller-pattern replicas have been realized from the master stamp with an array of hole patterns having a 400 nm hole size by tuning the filling ratio. We also demonstrate that an array of 30 nm graphene nanoribbons can be easily fabricated by exploring a hierarchical core–shell template structure employing a bilayer resist film via an EHL technique. The proposed minimal-contact patterning method is simple, versatile, and inexpensive and has potential to become a powerful technique for realizing feasible ultrafine nanostructures on a wafer scale.